Inovasi Program Jemput Pelayanan Keliling dalam Pembuatan Akta Kelahiran Oleh Dinas Kependudukan dan Catatan Sipil Kabupaten Pangandaran - Resti Illa Rahayu; Otong Husni Taufiq; Arie Budiawan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The public’s demand for excellent service encourages the government to continuously innovate. In response, the Population and Civil Registration Office of Pangandaran Regency developed an innovation called the mobile service pickup program. This innovation integrates offline services to accelerate and simplify the processing of population documents, particularly in the issuance of birth certificates. The mobile service pickup program is designed to improve the efficiency, effectiveness, and transparency of public services in the field of population administration in Pangandaran Regency. This study refers to the innovation theory by Everett M. Rogers, as cited in Prabowo H. (2022), which states that there are five attributes of innovation that influence its acceptance: relative advantage, compatibility, trialability, and observability. The research method used in this study is qualitative descriptive, with data collected through interviews, documentation, and observation. Meanwhile, informants were selected purposively to obtain relevant and in-depth data. The research results reveal that the mobile service pickup program innovation has not yet been optimally implemented, with time effectiveness being a crucial factor for the community. Therefore, this innovation must continue to be developed to gain wider acceptance among the public.